Analysis Of The Characteristic Of A Dual Chamber Microbial Fuel Cell Based On Copper Wire Mesh - Shavira Azzahra; Arya Kusuma Wardhana; Soraya Norma Mustika; Royb Fatkhur Rizal (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
Sustainable alternative energy solutions are being investigated as a result of the growing demand for energy worldwide and the negative effects of fossil fuels on the environment. A promising method is provided by Microbial Fuel Cell (MFC) devices, which use microbial activity to turn organic materials into electrical power. However, system configuration specifically, the distance between electrodes has a major impact on MFC performance. This study uses wastewater from rice washing as a substrate to examine the effects of different copper plate electrode spacings (1 cm, 3 cm, and 5 cm) on a dual- chamber MFC. By verifying the viability of using household organic waste for the generation of renewable energy and determining the ideal design parameters, this study advances MFC development. Copper plate and copper wire mesh electrodes, separated by a gel membrane, were utilized to create a self-assembled dual-chamber MFC. To assess system performance, measurements of voltage, current, power, and power density were made at various electrode distances and external loads. According to the findings, the maximum power output (207.5 mW), maximum voltage (0.467 V), and ideal power density (0.001395 mW/mg) were all achieved at a distance of 3 cm. Faster voltage stabilization was possible with a 1 cm gap, but efficiency was reduced with a 5 cm distance. At an external resistance of 3 kΩ, the system reached its maximum power.